Dampak Positif Penerapan Program Unggulan Pendidikan Bukittinggi (Pupb): Fikih, Akidah Akhlak, Sirrah Nabawiyah, Dan Bahasa Arab Dalam Pembelajaran Di Sdn 03 Pakan Labuah Bukittinggi - Annisa, Fitri; Ariza , Hidra; Puadi, Asral (Indonesian Research Journal on Education, 2023)
Islamic Religious Education is one of the Islamic religious-based education where the goal is to make students become a generation of Muslims who believe in Allah, have good morals, and are useful for the nation, state and religion. The implementation of the Bukittinggi Education Excellence Program is a policy implemented by the Bukittinggi city government which contains the application of additional Islamic religious-based subjects including fiqh, moral creed, sirrah nabawiyah, and Arabic. This flagship program applies to all elementary schools around the city of Bukittinggi. The aim of implementing thiseducation policy is to create students who have good morals and can deepen their religious knowledge. With the enactment of the Bukittinggi Education Excellence Program, it is hoped that educators can improve the morals and behavior of students in a better direction and increase students' understanding of religion more optimally so that they can apply their knowledge in everyday life. In other words, in order to realize superior students in general education and religious education.